WASTE BANK PROGRAM IN SUSTAINABLE DEVELOPMENT EFFORTS OF SEMARANG DISTRICT (Study in Soka Resik Waste Bank, Soka Hamlet, Lerep Village, West Ungaran Sub-District, Semarang Regency) - Setyarini, Shanaz Vindi; Subowo, Ari; Afrizal, Teuku (Journal of Public Policy and Management Review, 2021)
Sustainable development is a reference for global development in all development fields in Indonesia, especially those related to environmental sustainability. Solid waste pollution is a crucial problem that harms environmental sustainability, such as odor, water, air, and solid waste pollution. These problems need to be managed effectively with a specific approach, including a waste bank. The Waste Bank is a community empowerment-based effort that involves a Reduce, Reuse, and Recycling program using solid waste as an economic resource. Further, the waste bank program is also changing the paradigm from the "end of pipe" to the "reduction at the source" paradigm. This study focuses on solid waste management in Semarang Regency, specifically at the Soka Resik Waste Bank. Through qualitative research, observation, interviews, and secondary sources such as documents, journals, books, and research notes were carried out. The study found that the Waste Bank programs have reduced the amount of solid waste dumped in the TPA and recorded managed inorganic waste piles. In this context, the local government also provides support in education, assistance, guidance, and monitoring and infrastructure to the community. The Soka Resik Garbage Bank also has a significant impact on environmental aspects, but it still needs improvement in social and economic aspects. Hence, continuous and persistent education is urgent to change society's mindset massively by giving examples and submitting assistance to non-governmental organizations and the formation of MSMEs that sell crafts from recycling activities.